Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Purpose Lenalidomide is integral to multiple myeloma therapy, but long-term use is frequently complicated by diarrhea, which diminishes patient quality-of-life. The pathophysiology of lenalidomide-related diarrhea (LRD) is unclear, although bile acid (BA) malabsorption has been implicated. As the gut microbiota shapes BA metabolism, we evaluated whether perturbations of the microbiota and BA pool are associated with LRD. Experimental design In two prospective lenalidomide maintenance trials (NCT02538198 and NCT04497961), we profiled BAs, microbiota, dietary questionaries and patient-reported outcomes. Results Lenalidomide exposure was associated with increased fecal BA abundance; patients with LRD had enrichment of primary BAs without increased secondary BAs. LRD samples demonstrated reduced α-diversity and altered community composition, with reduced predicted BA-processing capacity. Baseline microbiota, BA and dietary profiles differed in patients who developed LRD, suggesting that pre-treatment features may influence LRD risk. Conclusions These findings implicate impaired microbial BA metabolism as a contributor to LRD and support investigating microbiota-targeted strategies to mitigate this toxicity.